Fuel cells for the long haul, batteries for the spurts [electric vehicles]. - Riezenman, M.J (IEEE spectrum)
Until only a few years ago, when environmentalists, automakers, and other concerned parties spoke about low-emissions vehicles, they were almost always referring to electric vehicles (EVs)-cars, trucks, and buses powered by batteries of one kind or another. Today, having so far failed in their quest for a battery that could make EVs practical, they are looking more and more to hybrid electric vehicles (HEVs), which automakers had hitherto rejected as merely an interim solution. But hybrids based on a combination of electric motors and internal combustion engines are attractive for two main reasons: they require no technology breakthroughs and no new infrastructure. They work with existing batteries since they do not rely on them for primary energy storage; rather, they can obtain fuel at any service station. An alternative to HEVs is fuel cell powered vehicles. The principles of this technology and the associated hydrogen storage issues are discussed. Other alternative fuels are briefly outlined